2021
DOI: 10.1007/s11109-021-09683-0
|View full text |Cite
|
Sign up to set email alerts
|

Propaganda, Presumed Influence, and Collective Protest

Abstract: Political propaganda can reduce citizens’ inclinations to protest by directly influencing their preferences or beliefs about the government. However, given that protest is risky in authoritarian societies and requires collective participation, propaganda can also reduce citizens’ inclination to protest by making them think that other citizens, rather than themselves, may have been influenced by propaganda and are, as a result, unwilling to protest. We test this indirect mechanism of propaganda using a survey e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Second, future studies could aim to replicate our study asking respondents how they think others would perceive the propaganda images. As illustrated by Huang & Cruz (2022) one mechanism of why propaganda has a deterrence e↵ect is that citizens believe that propaganda reduces the willingness of other citizens to protest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, future studies could aim to replicate our study asking respondents how they think others would perceive the propaganda images. As illustrated by Huang & Cruz (2022) one mechanism of why propaganda has a deterrence e↵ect is that citizens believe that propaganda reduces the willingness of other citizens to protest.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our survey results indicate very low levels of support for Maduro in line with his low approval ratings at the time, suggesting that respondents overall answered truthfully. Third, although the focus on Internet users does not allow us to generalize the results to the broader Venezuelan population, Internet users in Venezuela are of special importance as they have greater possibilities to inform themselves via independent sources, may be more likely to have an interest in politics, and potentially more willing to contend authoritarian practices (Huang & Cruz, 2022).…”
Section: Recruitment Ethical Considerations and Samplementioning
confidence: 99%
“…Kampanye hitam dan kampanye negatif akan merujuk pada terciptanya propaganda. Propaganda menjadi potensi buruk dalam dunia kampanye politik karena menyebarkan informasi yang tidak konkrit, terlalu dibesarbesarkan, dan dibentuk dengan senganja demi kepentingan salah satu pihak, propaganda bekerja pada tingkatan kolektif dan pribadi guna memanipulasi preferensi individu secara langsung dan meningkatkan dukungan terhadap seseorang (Huang & Cruz, 2022).…”
Section: Ketersediaanunclassified
“…A study of Chinese media found that propaganda also influences people's beliefs about other citizens' opinions on the regime. The likelihood of others protesting in turn impacted their own will to protest (Huang & Cruz, 2022). It is like Orwell states in his essay, Politics and the English Language: "Political language -and with variations this is true of all political parties, from Conservatives to Anarchists -is designed to make lies sound truthful and murder respectable and to give an appearance of solidity to pure wind (Blair, 2011)."…”
Section: Principles Of Propagandamentioning
confidence: 99%